Formation of ultrathin Ni germanides: solid-phase reaction, morphology and texture. (13th October 2017) - van Stiphout, K; Geenen, F A; De Schutter, B; Santos, N M; Miranda, S M C; Joly, V; Detavernier, C; Pereira, L M C; Temst, K; Vantomme, A
Abstract: The solid-phase reaction of ultrathin (⩽10 nm) Ni films with different Ge substrates (single-crystalline (1 0 0), polycrystalline, and amorphous) was studied. As thickness goes down, thin film texture becomes a dominant factor in both the film's phase formation and morphological evolution. As a consequence, certain metastable microstructures are epitaxially stabilized on crystalline substrates, such as the ϵ-Ni5 Ge3 phase or a strained NiGe crystal structure on the single-crystalline substrates. Similarly, the destabilizing effect of axiotaxial texture on the film's morphology becomes more pronounced as film thicknesses become smaller. These effects are contrasted by the evolution of germanide films on amorphous substrates, on which neither epitaxy nor axiotaxy can form, i.e. none of the (de)stabilizing effects of texture are observed. The crystallization of such amorphous substrates however, drives the film breakup.